Inhibitory Effects of Terfezia (Ascomycota) Desert Truffles on PANC-1 Cell Growth via Upregulation of Proapoptotic Genes TP53, CDKN1A, and BAX and Downregulation of Antiapoptotic Gene BCL2 - Saleh, Kochar Khasro; Kirbag, Sevda; Dalkilic, Semih (Begell House Inc, 2022)
Terfezia is an edible seasonal ectomycorrhizal fungus that has long been recognized as a delicacy in several regions of the world. Herein, aqueous extracts from three significant Terfezia species (T. claveryi, T. boudieri, and T. olbiensis) were investigated for their cytotoxic and apoptosis-induction effects on PANC-1 cells, a pancreatic cancer cell line. The MTT assay was applied to evaluate cytotoxicity. Quantitative real-time polymerase chain reaction (qRT-PCR) was performed to investigate genes associated with apoptosis, included four target genes (BAX, BCL2, CDKN1A, and TP53) and one reference gene (GAPDH). The aqueous extracts of T. claveryi, T. boudieri, and T. olbiensis exerted strong, dose-dependent inhibition of PANC-1 cell growth. Based on qRT-PCR, each extract reduced the progress of PANC-1 cells by inducing apoptosis, denoted by the upregulation of the proapoptotic genes BAX, CDKN1A, and TP53 and downregulation of the antiapoptotic gene BCL2. Ultimately, Terfezia desert truffles can be considered a functional and therapeutic food.
Keywords: Terfezia truffles; cytotoxic activity; MTT assay; qRT-PCR; gene expression; apoptosis; medicinal mushrooms